Neutral Effect of Increased Dairy Product Intake, as Part of a Lifestyle Modification Program, on Cardiometabolic Health in Adolescent Girls With Overweight/Obesity: A Secondary Analysis From a Randomized Controlled Trial - Skelly, Lauren E.; Barbour-Tuck, Erin N.; Kurgan, Nigel; Calleja, Melissa; Klentrou, Panagiota; Falk, Bareket; Josse, Andrea R. (Frontiers in Nutrition, 2021)
Background: The presence of obesity and some cardiometabolic disease risk factors in childhood and adolescence track into adulthood. Intake of dairy products has been shown to be inversely related to adiposity and cardiometabolic variables in youth. However, limited research has examined cardiometabolic disease risk factors following increased dairy product consumption as part of a lifestyle modification intervention in youth with overweight/obesity. This secondary analysis aimed to determine whether 12 weeks of increased dairy consumption, as part of a lifestyle modification program, affects cardiometabolic variables in adolescent females (range: 10-18 years) with overweight/obesity (BMI>85th centile). Methods: Participants were randomized into two groups: higher dairy intake (RDa; 4 servings/day [to reflect previous Canada’s Food Guide recommendations]; n=23) or low dairy intake (LDa; 0-2 servings/day; n=23). Both RDa and LDa participated in a 12-week, eucaloric, lifestyle modification intervention consisting of exercise training and nutritional counselling. Adiposity (percent body fat [%BF]), dietary intake, and measures of cardiometabolic health were measured pre- and post-intervention. Results: There were no significant changes over time within groups or differences over time between groups for triglycerides (TG), total cholesterol (TC), high-density lipoprotein cholesterol (HDL), TC/HDL ratio, low-density lipoprotein cholesterol (LDL), glucose, insulin, homeostatic model assessment of insulin resistance, adiponectin, and tumor necrosis factor alpha (TNF-α) (main effects of time and interactions, p>0.05). Leptin decreased over the 12-week lifestyle intervention in both groups (main effect of time, p=0.02). After combining the groups (n=46), significant correlations (p<0.05) were found between change in %BF and change in some cardiometabolic variables [HDL (r=-0.40), TC/HDL ratio (r=0.42), LDL (r=0.36) and TNF-α (r=0.35), p<0.05]. After controlling for change in dairy product intake, the correlations were unchanged. Conclusion: Our findings demonstrate that increased dairy product consumption, as part of a lifestyle modification, weight management intervention, had a neutral effect on cardiometabolic disease risk factors in adolescent females with overweight/obesity. Change in dairy product intake did not influence the relationships between change in adiposity and change in cardiometabolic variables. Future research designed to primarily assess the effect of increased dairy product consumption on cardiometabolic disease risk factors in this population is warranted. Trial registration: Clinicaltrials.gov; NCT#02581813.